Bangka Belitung Province Baznas Program in Efforts to Improve The Community Economy (Case Study of Sorgum Zakat Village In Beruas Village) - Bapaqih Alzikri; Sunaryati (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2024)
The declining level of the economy of the Bangka community in terms of declining selling prices of people's livelihoods that are not comparable to the purchase price of the basic needs of the community has caused many complaints from the public about this. Therefore the BAZNAS of the Province of Bangka Belitung has released a community empowerment program to improve the economy of the community through the zakat sorghum village program. The research method used in this study is descriptive qualitative. The objects in this study were the deputy chairman of two BAZNAS in the Bangka Belitung Islands Province, a field facilitator (third party) and mustahik who ran the sorghum zakat program. While the method in collecting data used is descriptive from the results of interviews of researchers to the speakers. The results of the study were through interviews with the deputy chairmen of two BAZNAS in the Bangka Belitung Islands Province, field assistants (third parties), and mustahik who carried out the sorghum zakat village program. first implementation of the program, third, parties submitted proposals to BAZNAS, secondly, village and mustahik determination, third, field survey, fourth, submission of BAZNAS funds, and fifth, mentoring process. For the impact of the implementation, the impact is not very significant for the mustahik because this program is new and is still in the process of testing, of course there are many things that mustahik do not understand in running the program. As for the obstacles faced in implementing the sorghum zakat village program are constraints on land, sparrows, and mice.